The relationship between trajectories of intrinsic capacity and differences in the risk of functional ability decline in community-dwelling older adults: A socio-ecological approach - Shin, Ji Hye; Sagong, Hae; Yoon, Ju Young (Archives of gerontology and geriatrics, 2025)
•The intrinsic capacity (IC) exhibits considerable heterogeneity.•The trajectories of impaired IC (IIC) were categorized into four classes.•The IIC trajectory affected the risk of functional ability (FA) decline.•Multiple factors have overlapping effects on IIC trajectories and FA decline. Functional ability (FA), a key determinant of healthy aging, is determined by intrinsic capacity (IC), environmental factors, and their interactions. IC is a composite of physical and mental capacities that undergo constant change. Therefore, understanding the factors that influence IC requires a multi-level analysis of individuals to optimize its trajectory. Individuals aged ≥ 65 were included in the Korean Longitudinal Study of Aging (2012–2020). Impaired IC (IIC) scores were tracked over eight years using latent class growth modeling to classify trajectory patterns. Determinants were identified through multinomial logistic regression. The relationship between IIC trajectory and FA decline was assessed using Kaplan-Meier analysis and the Cox proportional hazards model. Of the 7486 subjects, 2268 (mean age 72.26 [SD 5.31] years; female 56.4 %) were included after excluding those who were underage, had lost independence, or were missing baseline data. The IIC trajectories were categorized into four classes: low-persistent (Class 1, 48.46 %); low-increasing (Class 2, 17.46 %); high-decreasing (Class 3, 20.37 %); and high-stable (Class 4, 13.71 %). Over a mean follow-up of 7.21 years, 536 individuals experienced a decline in FA. After adjusting for confounders, the hazard ratios (HRs) were 1.95 (95 % CI 1.51–2.50) for class 2, 1.93 (1.50–2.46) for class 3, and 3.41 (2.64–4.39) for class 4 compared to class 1. Additionally, age, gender, marital status, employment, social participation, and living status had overlapping effects on both IC and FA. Understanding the heterogeneity of IC, combined with multidomain interventions, can enable FA maintenance and promote healthy aging.